Magnetic excitations in the stripe phase of high-T-c superconductors - Schmidt, Kai Phillip; et al. (ELSEVIER SCIENCE BV, 2005)
The magnetic excitations in the stripe phase of high-T-c superconductors are investigated in a model of spin ladders which are effectively coupled via charged stripes. Starting from the effective single-triplon model for the isolated spin ladder, the quasi-one-dimensional spin system can be described straightforwardly. Very good agreement is obtained with recent neutron scattering data on La15/8Ba1/8CuO4 (no spin gap) and YBa2Cu3O6.6 (gapped). The signature of quasi-one-dimensional spin physics in a single-domain stripe phase is predicted. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: superconductors; high T-c; neutron scattering; inelastic; antiferromagnetism; quantum; spin dynamics